ANALISIS SISTEM INFORMASI AKUNTANSI PENJUALAN DAN PENERIMAAN KAS UNTUK MENINGKATKAN PENGENDALIAN INTERNAL DI UD PROJECT POT KEDIRI - Putri, Anggun Utomo; Puspita, Erna; Sugeng, Sugeng (Universitas Nusantara PGRI Kediri, 2022)
The purpose of the study was to find out a series of sales accounting information systems as well as cash receipts and internal control systems that have been applied to the UD Project Pot. This research uses qualitative methods, using primary data. Data collection procedures through observation, documentation and interviews, the analysis technique of this research is descriptive qualitative. The result of the research is that the implementation of the sales accounting information system and cash receipts are still not good, due to the limitations of functions, the lack of completeness of the documents used. The analysis of the system of accounting for cash sales and cash mining contained in internal control is also not good, as can be seen from the absence of a full stamp on the invoice and the stamp has been submitted in the delivery function, then cash from cash sales is not paid to the bank on the same day as the cash sales transaction.